Viscera Characteristics of MSTN-Edited Heterozygous Pigs - Pei, Yangli; Fan, Ziyao; Song, Yuxin; Chen, Chujie; Mu, Yulian; Li, Bugao; Feng, Zheng; Li, Hua; Li, Kui (Frontiers in Genetics, 2022)
Myostatin (MSTN) is a protein that negatively regulates growth of skeletal muscle, and inactivation of myostatin improves the mass of skeletal muscle. Pigs with a naturally occurring single copy MSTN mutation have higher muscle depth and lower fat depth compared to wild type. Therefore, MSTN-edited pigs are most likely to appear as heterozygotes in the potential future market, but the visceral development of pigs with MSTN gene editing remains unclear. Here, we investigated the histological morphology of the viscera in MSTN gene heterozygotes at newborn and adult stages. The sizes and weights or length of organs were further compared between adult heterozygous and wild type pigs. We found no significant differences in histomorphology of major organs between individuals from two genotypes at newborn and adult stages. Moreover, there was no significant difference in the size and average weights or length of visceral organs in adult pigs. Our data provide a reference for further clarifying the applications of MSTN gene edited pigs.